Biotechnology: The Future As Viewed by Land-Grant University Administrators - Clifton Anderson (Journal of Applied Communications, 1992)
Research Directors at American Land-Grant Universities are optimistic regarding the future agricultural biotechnology and expect the ongoing "biotechnology revolution" to benefit the public, including consumers and farmers.